Recepcja poglądów Johna Ruskina na wychowanie w Polsce przełomu XIX i XX wieku - Lisiecka, Alicja (Biuletyn Historii Wychowania, 2020)
The purpose of this article is to show the reception of the educational views of John Ruskin (1819–1900) presented in Polish scientific literature at the turn of the XIX and XX century. John Ruskin was an great English writer, poet, painter and critic of art and social reality. Ruskin’s oeuvre, contained in numerous writings, is the result of admiration for the world, reflection on landscapes, art and timeless values: truth, goodness and beauty; he’s works are characterized by individualism, momentum, normativity, and literary style full digression. For Ruskin, there is no clear definition of education and the educational system. Educational process itself is described in general terms. Ruskin’s beliefs about art and society are connected with the issue of children’s raising. The article contains numerous quotes – from the publications of Polish authors, translations and original Ruskin’s works – enriching the exemplification of the problem outlined in the subject of this article. Ruskin’s thoughts can be found in the foundations of progressive pedagogy and active pedagogy. For this reason, it is worth to consider the issue of the reception of educational views of Ruskin presented in Poland in years 1897–1936.